Modelling the effect of 2-4, D on the growth kinetics of cell suspension cultures of Ficus deltoidea L - Ling, Anna Pick Kiong; Halmi, Mohd. Izuan Effendi; Hussein, Sobri; Ong, S. L. (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
The mistletoe fig (Ficus deltoidea) is frequently found in several areas of the world, and primarily functions as houseplant or an ornamental shrub. The plant is discovered indigenous generally in Asia tropical region for example Indonesia, Philippines, Malaysia, and Thailand. Scientific studies on the effect of plant growth regulators on cells production from this plant are vital as optimization of cells production may result in effective production of secondary products characterization and output. The growth of cell suspension cultures from this plant shows sigmoidal property. In this work, we model the effect of the plant growth regulator 2,4-dichlorophenoxyacetic acid (2,4-D) on the growth kinetics of the cells from this plant according to the modified Gompertz model. The coefficient of determination showed good agreement between experimental and predicted data with values ranging from 0.97-0.98. The results showed that 2,4-D at 2 mg/L was optimal for achieving the highest cells growth rate. It is anticipated that the growth parameter constants extracted from the modelling exercise will be helpful in the future for additional secondary modelling on the effect of media conditions as well as other factors on cells growth